2020
DOI: 10.1038/s41540-020-00150-w
|View full text |Cite
|
Sign up to set email alerts
|

ROS networks: designs, aging, Parkinson’s disease and precision therapies

Abstract: How the network around ROS protects against oxidative stress and Parkinson’s disease (PD), and how processes at the minutes timescale cause disease and aging after decades, remains enigmatic. Challenging whether the ROS network is as complex as it seems, we built a fairly comprehensive version thereof which we disentangled into a hierarchy of only five simpler subnetworks each delivering one type of robustness. The comprehensive dynamic model described in vitro data sets from two independent laboratories. Notw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 119 publications
(197 reference statements)
1
41
0
Order By: Relevance
“…OXPHOS also generates potentially toxic byproducts in the form of ROS, which, if not tightly regulated by antioxidant defenses, can disrupt mitochondrial physiology, damage DNA, modify protein functions, cause lipid peroxidation, and negatively influence signaling pathways including transcriptional regulation [ 47 , 48 ]. Hence, all mitochondrial processes can be impacted by unbalanced ROS regulation and may thus represent a common pathway/potential starting point for neurodegenerative diseases [ 49 , 50 , 51 ]. Neurons are characterized by a high metabolic demand and require reliable ATP synthesis for diverse neuro-communication functions including maintenance of resting membrane potential, neurotransmitter synthesis and release [ 52 ], thus, disruption of this process is particularly detrimental to neuron health and survival.…”
Section: Discoveries Of Mitochondria-specific Phenotypes In Ipsc Models Of Pdmentioning
confidence: 99%
“…OXPHOS also generates potentially toxic byproducts in the form of ROS, which, if not tightly regulated by antioxidant defenses, can disrupt mitochondrial physiology, damage DNA, modify protein functions, cause lipid peroxidation, and negatively influence signaling pathways including transcriptional regulation [ 47 , 48 ]. Hence, all mitochondrial processes can be impacted by unbalanced ROS regulation and may thus represent a common pathway/potential starting point for neurodegenerative diseases [ 49 , 50 , 51 ]. Neurons are characterized by a high metabolic demand and require reliable ATP synthesis for diverse neuro-communication functions including maintenance of resting membrane potential, neurotransmitter synthesis and release [ 52 ], thus, disruption of this process is particularly detrimental to neuron health and survival.…”
Section: Discoveries Of Mitochondria-specific Phenotypes In Ipsc Models Of Pdmentioning
confidence: 99%
“…Such a graph can be translated into mathematical equations that, when simulated, may lead to the identification of temporal mechanisms of GCBC differentiation. We have recently illustrated this for the network underlying cell cycle control and reactive oxygen species (ROS) production where we discovered new regulatory patterns (213,214). The intracellular regulatory network involved in the positive selection of GCBCs should be modeled similarly as a multi-component, temporally evolving dynamic system.…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al observed a basal NRF2 cytosol-nucleus oscillation behavior in cells with a period of about 2 hours for which they constructed a mathematical model of negative feedback through NRF2 phosphorylation and dephosphorylation without involving changes in the abundance (Xue et al 2015). Kolodkin et al has recently incorporated the KEAP1-NRF2 component into an ROS dynamic network to explore the design principles relevant to network-based therapies for Parkinson disease (Kolodkin et al 2020). Compared to the previous work, our present study provided a much more detailed analysis of the KEAP1-NRF2 module itself, which can be adapted and included in future systems-level models of antioxidant and detoxification responses.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modeling plays a crucial role in understanding and predicting the quantitative behavior of redox pathways (Adimora et al 2010, Selvaggio et al 2018). Earlier modeling work including our own has included the KEAP1-NRF2 module in the larger context of the NRF2-mediated antioxidant response pathways (Zhang and Andersen 2007, Zhang et al 2009, Hamon et al 2014, Leclerc et al 2014, Khalil et al 2015, Xue et al 2015, Kolodkin et al 2020). However, in most of these studies the KEAP1-NRF2 module was treated as simplified degradation network motifs, yet the details of KEAP1-NRF2 interactions and especially the likely nonlinearity in signaling have not been explicitly and fully explored.…”
Section: Introductionmentioning
confidence: 99%